2005
DOI: 10.1093/nar/gki315
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic and site-specific modification of endocyclic nitrogen atoms of purines in DNA and its potential for biological and structural studies

Abstract: Site-specific modification of the N1-position of purine was explored at the nucleoside and oligomer levels. 2′-Deoxyinosine was converted into an N1-2,4-dinitrophenyl derivative 2 that was readily transformed to the desired N1-substituted 2′-deoxyinosine analogues. This approach was used to develop a post-synthetic method for the modification of the endocyclic N1-position of purine at the oligomer level. The phosphoramidite monomer of N1-(2,4-dinitrophenyl)-2′-deoxyinosine 9 was prepared from 2′-deoxyinosine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Its binary mixtures are employed in high-performance thin layer chromatography, for example, in the process of separation of biological compounds. [1][2][3][4] Chemically, p-anisaldehyde is produced through liquid-phase oxidation of p-methoxy-toluene. 5 p-Anisaldehyde has been reported to dimerize readily in solution due to hydrogen bond formation, [6][7][8] and it is suggested that a charge transfer from the methoxy group to the aldehyde group is responsible for this type of aggregation.…”
Section: -Methoxybenzaldehyde (Known Also As P-anisaldehyde)mentioning
confidence: 99%
“…Its binary mixtures are employed in high-performance thin layer chromatography, for example, in the process of separation of biological compounds. [1][2][3][4] Chemically, p-anisaldehyde is produced through liquid-phase oxidation of p-methoxy-toluene. 5 p-Anisaldehyde has been reported to dimerize readily in solution due to hydrogen bond formation, [6][7][8] and it is suggested that a charge transfer from the methoxy group to the aldehyde group is responsible for this type of aggregation.…”
Section: -Methoxybenzaldehyde (Known Also As P-anisaldehyde)mentioning
confidence: 99%
“…Structures and the conventional numberings of these three nucleosides are shown in Scheme 1. In our recent work, [12] we have developed a novel method to prepare oligodeoxyribonucleotides (oligomers) containing modified purines. One of the key compounds was N1-dinitrophenyldeoxyinosine 4 that was prepared from 3 and subsequently converted into various purine-modified nucleosides (5)(6)(7)(8) as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] Recently, we reported a simple protocol for site-specific 15 N-labelling of nucleosides and oligomers containing modified purine. [12] As an example, treatment of N1-dinitrophenyl-2 -deoxyinosine 4 with 15 N-labelled ammonia gave the desired product, N1-15 N-labelled deoxyinosine 5 (Scheme 2).…”
Section: Exploitation Of Site-specific Isotopic 15 N-labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…There have already been shown that N 1 -(2,4-dinitrophenyl (or 4-nitrophenyl))inosines with primary alkylamines afford N 1 -alkyl inosines via an ANRORC mechanism. [5][6][7][8][9] Here we have described the reaction of 3 with primary alkylamines in detail.…”
mentioning
confidence: 99%